(untitled) (Journal of Leadership, Accountability and Ethics, 2023)
Research on the coexistence of contradictory traits has predominantly examined the interpersonal consequences of such personality complexity with minimum focus on within-person dynamics. This study investigates the cognitive process through which narcissism and humility coexist and interact to shape individuals’ psychological entitlement. Drawing from self-concept theory and paradox theory, we propose that elevated levels of humility attenuate the relationship between narcissism and psychological entitlement. We conducted hierarchical linear regression analyses and simple slope tests using a sample of 451 individuals (47.2 % female) from a North American university. Our results suggest that humility effectively mitigates the impact of narcissism on psychological entitlement. Our study furthers the understanding of dynamic interplay between contradictory traits, contributing to both self-concept literature and the paradox theory through theoretical integration. We underscore the value of employing paradox theory in micro-level research that delves into the dynamic cognitive process within individuals.